Clinical evaluation of class II Targis inlays: preliminary results after 1 year - (:unkn) unknown (WILEY, 2003)
The aim of this study was to evaluate the clinical performance of a new generation of restorative resin, Targis (Vivadent), in class II inlay restorations. Forty class II Targis inlays were placed (18 premolars, 22 molars) in 26 patients (mean age=25.5). All test teeth were vital. All restorations were in occlusion and were placed adhesively using Variolink II high viscosity (Vivadent) in combination with Syntac adhesive system under rubber-dam by the same operator. The restorations were evaluated at baseline and after 6 months and 1 year, according to modified United States Public Health Service (USPHS) criteria by two examiners. The parameters evaluated were: anatomical form, marginal adaptation, marginal discoloration, colour match, surface finish, gingival index and secondary caries. Post-operative sensitivity was determined by direct questioning. Regarding all of the clinical evaluation criteria all 40 inlays exhibited clinically acceptable scores after 1-year evaluation period. Relying on these early 1-year results, the new restorative material (Targis) seems to be promising in class II inlays.
Keywords: inlay; composite resin; clinical performance; CERAMIC INLAYS; COMPOSITE RESTORATIONS; ONLAYS